Local buckling strength of stiffened box sections in combined compression and bending - Somsak Poovarodom; Usami, Tsutomu; Federal Republic of Germany (DAAD) (BangkoK : Asian Institute of Technology, 1977)
A theoretical study is presented on the elastic and inelastic local buckling strength of longitudinally stiffened box sections in combined compression and bending. Particular attention is paid to the effects of welding residual stresses on the buckling strength of such sections. The finite strip method is employed to obtain the stiffness and geometric matrices of a buckled box section based on the deformation theory of plas ticity. The effective rigidity of a buckled longitudinal stiffener is evaluated based on the tangent modulus theory. In the numerical study, elastic buckling of unstiffened and stiffened box sections is first discussed. Optimum proportion of cross-section and the effects of longitudinal stiffeners are the major subjects in the discussion. Finally, inelastic buckling of stiffened box sections is discussed in comparison with that of isolated stiffened plates.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Buckling (Mechanics)